Multi-Segment Crash Box Energy Absorption Ability Using Computer Simulation - Halman Halman (MEDIA PERSPEKTIF : Journal of Technology, 2020)
Crash box is one of the passive safety components in vehicles, especially cars that are designed to reduce the occurrence of injuries to drivers and passengers due to collisions. This study aims to determine the energy absorption of the crash box with a multi-segment circular cross section. The research method used is quasi-experimental, namely by computer simulation using Finite Element Method-based software. The independent variable in this study is the location of the segment connection, including: 1/4, 1/3, and 1/2 of the total length of the crash box. While the dependent variables that are sought include: energy absorption, force reaction, and deformation patterns that occur in the crash box. The crash box will be hit by an impactor with a mass of 103 kg and a speed of 7.67 m/s. From the simulation results, the maximum energy absorption and force reaction values are found in the crash box at connection 1/2 of 1689.7 J and 67718 N, followed by connection 1/3 with values of 1221.2 J and 56127 N, and the last is at 1/4 connection is 1119.8 J and 55443 N. Judging from the deformation pattern, the connection at 1/4 and 1/3 is buckling so that the energy absorption is lower than the crash box at the 1/2 connection. It is concluded that the most optimal design of the crash box with a multi-segment circular cross section is the model at the 1/2 connection because it has the highest energy absorption value of the other 2 models and the deformation tends to be more stable.